Antagonist agents in opiate addiction: naltrexone - Kalyoncu, Ayhan; Mırsal, Hasan; Satır, Tulga (Journal of Dependence, 2000)
Naltrexone is a spesific opioid antagonist that has a relatively long duration of action such that it can be used in aiding in the prevention of relaps to opioid dependence. Naltrexone is safe and relatively non-toxic.The antagonist treatment option is important to make available to well-motivated addicted individuals who desire to become drug free.As with all medication in the treatment of addiction, naltrexone must be used within a comprehensive treatment program, including individual or family psychotherapy and urine testing for illicit drugs.treatment should be continue for at least 3 months after detoxification and in many cases longer because there is a significant risk of relaps continuing for several years. There are many resarches in medications development.Several medications currently under study will add to the options for treatment in next several years.A depot form of naltexone that gives protection against relaps for 30-60 days is under study.Recent clinical trials in alcoho- lies suggest that naltexone may reduce the frequency of relapse in an outpatient rehabilitation program.